Analisis Akad Mudharabah Dalam Fasilitas Pendanaan Jangka Pendek Syariah Pada Bank Syariah Mandiri - Ike Purnamasari (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
Islamic Banking began to grow rapidly since 2001, in line with these developments required an Islamic Short Term Funding Facility (FPJPS), with mudharabah mechanism provided by the central bank, Bank Indonesia, so that the value of the liquidity of Islamic banking especially Bank Syariah Mandiri increased. This research is descriptive qualitative using data and information as well as the study of literature / bibliography. This study was elaborated on the Islamic Short Term Funding Facility (FPJPS) mechanism mudharabah and Bank Syariah Mandiri how to respond to the Islamic Short Term Funding Facility